Production of β-lactoglobulin (BLG) gene knock- out blastocyst stage embryos of Indian water buffalo using CRISPR and SCNT technology - Aseem Tara; Priyanka Singh; Devika Gautam; Gaurav Tripathi; Shreya Malhotra; Sacchinandan De; Manoj K. Singh; Naresh L. Selokar (Revista Científica)
In several tropical countries, buffalo milk has a higher-value demand than cow milk due to its nutritional and economic value. In India, the buffalo is the main dairy animal and contributes 45% of the total milk produced in the country. Besides the nutritional value of milk, several allergen proteins such as casein, α-lactalbumin, β- lactoglobulin (BLG), and immunoglobulins have been reported. Breeding strategies, nutritional management, and quantitative genetics have improved milk yield, but these approaches could not lead to significant changes in milk composition. With the development of biotechnology, especially genome editing tools (CRISPRs), it is possible to generate new value-added products such as designer hypoallergenic milk for human health benefits. Keeping this in mind, we planned to utilize the CRISPR tools to disrupt the buffalo β-lactoglobulin (BLG) gene to produce hypoallergenic milk in the long run. In pursuit of our objectives, we designed three single guide RNAs (sgRNAs) targeting the BLG locus in buffalo. Subsequently, we assessed their editing efficiency through a combination of Sanger sequencing, followed by TIDE and ICE analysis. Among three sgRNAs, the most efficient sgRNA was used to generate the clonal population of edited cells. Several single-cell clones were established and screened using the TA cloning (also known as rapid cloning or T cloning) and Sanger sequencing methods. Of 14 single-cell clones screened, eight were found to have BLG gene disruption events (57% editing rates). Using SCNT, we successfully produced cloned blastocyst stage embryos from 4 BLG-gene disrupted clonal cells. The cloned blastocyst production rates (25 to 30%) were similar to non-edited control cells. Efforts are ongoing to establish pregnancies from BLG-KO cloned embryos. This work can lead to the generation of designer buffaloes to produce hypoallergenic milk for human benefit.